2017
DOI: 10.1155/2017/9324246
|View full text |Cite
|
Sign up to set email alerts
|

Sport-Related Portal Vein Thrombosis: An Unusual Complication

Abstract: Portal vein thrombosis (PVT) is an uncommon condition usually associated with hypercoagulable states or liver cirrhosis. PVT due to sports-related injuries is rarely reported and, to the best of our knowledge, only two cases have been reported thus far. Brazilian jiu-jitsu (BJJ) is a form of martial arts and is considered very safe with minimal risk for injury. It has growing popularity worldwide. Here, we report the first case of PVT secondary to abdominal trauma related to the practice of (BJJ) in an otherwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Noncirrhotic, nonmalignant PVT is rare and is usually associated with infection, trauma, or prothrombic disorder. In about 25 percent of cases, the etiology remains elusive despite extensive workup [3]. Pylephlebitis (suppurative thrombophlebitis of the portal vein) is a rare complication of intra-abdominal or pelvic infection [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noncirrhotic, nonmalignant PVT is rare and is usually associated with infection, trauma, or prothrombic disorder. In about 25 percent of cases, the etiology remains elusive despite extensive workup [3]. Pylephlebitis (suppurative thrombophlebitis of the portal vein) is a rare complication of intra-abdominal or pelvic infection [4].…”
Section: Discussionmentioning
confidence: 99%
“…Lemierre's syndrome is a classic example of human necrobacillosis wherein acute primary infection of oropharynx is followed by secondary septic thrombophlebitis of internal jugular vein and subsequent septic embolization at various sites [2]. Pylephlebitis (suppurative, infected portal vein thrombosis (PVT)) is a rare but serious complication of intra-abdominal or pelvic infection and is associated with significant morbidity and mortality [3,4]. Pylephlebitis due to F. necrophorum, also known as abdominal variant of Lemierre's syndrome, has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, PVT has been related to sports injuries. Dumic et al reported a case of PVT secondary to abdominal trauma related to the practice of brazilian jiu-jitsu in a 32-year-old man with no other traditional risk factors for PVT [ 71 ]; other cases have been described as correlated with decompression sickness in a 48-year-old deep sea self-contained underwater breathing apparatus (SCUBA) diver [ 72 ] and with kickboxing [ 73 ].…”
Section: Risk Factors For Portal Vein Thrombosismentioning
confidence: 99%
“…(5) Trauma: Severe abdominal or liver trauma can damage the portal vein and initiate clotting. There have even been reports of portal vein thrombosis related to abdominal trauma [6] and injuries associated with sports activities [7].…”
Section: Introductionmentioning
confidence: 99%